Analisis Tingkat Kepentingan Desain Industri Produk Handphone: Studi Kasus di Fakultas Ekonomi Ubinus - Budiastuti, Dyah; GF, Diananda (Journal the Winners: Economics, Business, Management, and Information System Journal, 2006)
Article present the importance of industrial design on handphone product that today it becomes one of most popular communication tools. The research used qualitative descriptive method on handphone product that most likely used by Faculty of Economics students of Bina Nusantara University. The research result shows that the role of industrial design in handphone product development has higher interest in fulfilling theergonomic needs compare to the role in fulfilling the aesthetic needs.